Orbitary fracture caused by rubber project: Case report (Research, Society and Development, 2021)
Rubber projectiles are used, usually by police and private security entities, in the search for better control of demonstrations, riots or rebellions. Considered less lethal weapons than firearms, such devices can cause devastating bodily injuries, with aesthetic, functional and social consequences unimaginable to the target. The use of this instrument must follow recommendations carefully in order to avoid and / or minimize damage. The ballistic injuries that affect the maxillofacial region are a challenge for the buccomaxillofacial surgeon, due to its high degree of complexity, and anatomical identification of the damaged tissues, understanding of the limitations of this type of injury, the preservation of skeletal tissues and soft. Thus, awareness of the harmful potential of this instrument should be a priority in the quest to minimize injuries arising from it. The purpose of this article is to report the clinical case of an orbital fracture caused by a rubber projectile, as well as to discuss the morbidity potential of this instrument.